2003
DOI: 10.1097/01.brs.0000083165.93936.6d
|View full text |Cite
|
Sign up to set email alerts
|

Boston Brace Correction in Idiopathic Scoliosis: A Biomechanical Study

Abstract: High thoracic pads reduced more effectively both thoracic and lumbar scoliotic curves than lumbar pads only. The study suggests that mechanisms other than brace pads produce correction and contribute to the force equilibrium within the brace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 19 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…Previous modeling works evaluated the thoracic region focusing on corrective treatments of scoliosis (Grealou et al, 2002; Aubin et al, 2003; Perie et al, 2003; Duke et al, 2005; Salmingo et al, 2012; Curtin and Lowery, 2014). Furthermore, spine models developed for load estimation were mostly oriented to explore lumbar region, describing thorax as a single rigid body (Stokes and Gardner-Morse, 1995; Shirazi-Adl et al, 2005; de Zee et al, 2007; Arjmand et al, 2009; Christophy et al, 2012; Han et al, 2012; Ghezelbash et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous modeling works evaluated the thoracic region focusing on corrective treatments of scoliosis (Grealou et al, 2002; Aubin et al, 2003; Perie et al, 2003; Duke et al, 2005; Salmingo et al, 2012; Curtin and Lowery, 2014). Furthermore, spine models developed for load estimation were mostly oriented to explore lumbar region, describing thorax as a single rigid body (Stokes and Gardner-Morse, 1995; Shirazi-Adl et al, 2005; de Zee et al, 2007; Arjmand et al, 2009; Christophy et al, 2012; Han et al, 2012; Ghezelbash et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A biomechanical study by Perie et al [41] has evaluated the effectiveness of the Boston brace using finite element model and experimental measurements. It highlighted the contribution of bracing pads to curve reduction but also suggested that other mechanisms participated in orthotic correction.…”
Section: Methods Developed To Assist Bracing Treatmentmentioning
confidence: 99%
“…Brace manufacturing has been transformed by computer-assisted modelling and manufacture by using 3D laser scanners to obtain patient torso data and directly carve out a mould for a brace [23,24]. For fitting braces, finite element computer models have been developed that may analytically test multiple types of braces to determine the optimal amount of force and pad placement within the brace [25][26][27][28][29][30][31][32][33]. Ultrasound has also been used to evaluate curve correction while patients are in a brace to check the efficacy of a brace in real time [34,35].…”
Section: Guidelines For Bracing Studiesmentioning
confidence: 99%